Antibacterial activity of zinc oxide nanoparticles obtained by pulsed laser ablation in water and air - Goncharova, Darya A.; Gavrilenko, Ekaterina A; Nemoykina, Anna L.; Svetlichnyi, Valerii A. (MATEC Web of conferences)
The paper studies physicochemical and antibacterial properties of ZnO nanoparticles obtained by pulsed laser ablation in water and air. Their composition and structure were studied by X-ray diffraction, transmission and scanning electron microscopy. Antibacterial activity of the nanoparticles was examined by its affection on Gram-positive Staphylococcus aureus (S.aureus). The dependence of nanoparticles' physical and chemical antibacterial properties on the conditions of the ablation was shown. The model materials for the antibacterial bandage were made of cotton, filter paper and biodegradable polymer scaffolds (poly-l-lactide acid), and then they were coated with the obtained ZnO nanoparticles. The model bandage materials were examined by the scanning electron microscopy method and their antibacterial activity (ISO 20743:2013) was determined. High activity of all the samples against S.aureus was proved.